DATUM - Interface eletrônica como meio de expressão da experiência - CARVALHO, Márcio Lins de (Universidade Federal do Pará, 2024)
This thesis addresses the experience of creating an experimental electronic game (game, for mobile devices, cell phones) called “DATUM” (work in process) developed from and during the doctorate period. These writings and their annexes address three different and complementary perspectives: the first on reflections on method and artistic creation in the academy; the second on the theoretical conceptions derived from the artistic creation of electronic games; the third on the sub-processes and hazards of game development; in addition to these, the thesis is also composed of the game itself. Taking these perspectives, the thesis proposes to experiment with the image, in the abstract sense, using a dynamic of building constellations to incite the projection of images by connecting stars; and the virtual with its interactive possibilities within a three-dimensional space.